UV sunscreens of microbial origin: mycosporines and mycosporinelike aminoacids - Colabella, Fernando (2014)
Exposure to ultraviolet radiation (UVR) is harmful to living organisms, causing damage to macromolecules such as DNA, RNA, proteins and lipids. Depending on the wavelength, the injury could be direct or indirect through reactive oxygen intermediates, so it is desirable to find compounds that can reduce both. Many organic chemicals used in commercial sunscreen possess estrogenic activity in vivo. In this report we analyzed recent patents related to UV sunscreens of microbial origin, in particular mycosporines (MYC) and mycosporine-like aminoacids (MAA). Both are promising natural alternatives for both direct (UV-absorption) and indirect (antioxidant) protection, given they show strong photostability and absence of cytotoxicity. It becomes clear that although the search for natural photoprotective molecules is relatively recent, efforts have been invested mainly in marine environments, remaining still many potential photoprotective molecules to find in other type of habitats. Furthermore, unicellular microorganisms have several advantages for the production of metabolites of interest, since they improve the production costs due to its simplicity of culture and easy genetic manipulation. The knowledge of the biosynthesis pathway of MYC and MAA is essential to improve rationally their expression levels. Currently, only the MAA pathway in bacteria has been reported, remaining the MYC pathway unclear. Future perspectives include the heterologous expression of MYC and/or MAA in industrially friendly microorganisms (bacteria and yeast) in order to co-produce different UV-protective molecules and thus cover a broader UV spectrum and simplify the production process.